2022
DOI: 10.1002/adfm.202206513
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Synergies in Bimetallic RuPt Single–Atom Catalysts via Speciation Control

Abstract: Bimetallic single-atom catalysts (b-SACs) have recently gained prominence by virtue of the unique catalytic cooperative interactions they can exhibit, intertwining electronic and geometric effects. To date, research efforts have exclusively focused on direct mechanisms such as electron density transfer or sequential reactivity. Herein, the first study on indirect, coordination-induced catalytic synergies in carbon-supported RuPt SACs is conducted. To this end, a holistic approach is developed, combining i) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…To represent the wide range of possible chemical environments in NC, speciation analysis of Pd over the NC cavities is conducted by calculating Boltzmann distributions of the chlorinated Pd species, deriving from the H 2 PdCl 4 precursor employed in the synthetic procedure (Tables S5 and S6). To this end, tri-pyrrolic (3 × N5) and tetra-pyridinic (4 × N6) sites are selected as representatives of trigonal and square-planar geometries (Figure S19), respectively, in line also with literature-reported studies. , The calculated distribution demonstrates that chlorinated species (PdCl x , x = 1–4) tend to adsorb on 3 × N5 sites (41–94% of the Boltzmann population), although upon thermal treatment, Pd SAs are preferably stabilized on square-planar 4 × N6 sites, reflected by a significant reduction in the calculated Boltzmann population (up to 8%). While the EXAFS analysis of Pd SA /NC (Pd-N CN = 4.4, Table S1) derived from EXAFS fitting would suggest stabilization of the Pd atoms on 4 × N6 sites, the square-planar geometry of this configuration leads to virtually inactive metal sites (Table S7).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…To represent the wide range of possible chemical environments in NC, speciation analysis of Pd over the NC cavities is conducted by calculating Boltzmann distributions of the chlorinated Pd species, deriving from the H 2 PdCl 4 precursor employed in the synthetic procedure (Tables S5 and S6). To this end, tri-pyrrolic (3 × N5) and tetra-pyridinic (4 × N6) sites are selected as representatives of trigonal and square-planar geometries (Figure S19), respectively, in line also with literature-reported studies. , The calculated distribution demonstrates that chlorinated species (PdCl x , x = 1–4) tend to adsorb on 3 × N5 sites (41–94% of the Boltzmann population), although upon thermal treatment, Pd SAs are preferably stabilized on square-planar 4 × N6 sites, reflected by a significant reduction in the calculated Boltzmann population (up to 8%). While the EXAFS analysis of Pd SA /NC (Pd-N CN = 4.4, Table S1) derived from EXAFS fitting would suggest stabilization of the Pd atoms on 4 × N6 sites, the square-planar geometry of this configuration leads to virtually inactive metal sites (Table S7).…”
Section: Resultsmentioning
confidence: 68%
“…For the simulation of the SACs, a Pd atom was placed on the N-cavity of the selected carbon-based hosts. Tri-pyrrolic (3 × N5) and tetra-pyridinic (4 × N6) sites are selected as representatives of trigonal and square-planar geometries, respectively, in agreement also with literature-reported studies . Speciation analysis of Pd over the distinct cavities of NC was performed via Boltzmann distribution calculations taking into account different degrees of chlorination of the Pd atom, in order to simulate the synthetic conditions .…”
Section: Methodsmentioning
confidence: 99%
“…Although the number of studies covering the integration of multiple metal sites is rapidly increasing, reporting diverse electronic cooperative mechanisms between metal centers, general geometry-electronic property relations have not yet been unraveled. While the intersite distance has been proposed as a descriptor to quantitatively evaluate the electronic metal–metal interactions, 84 , 87 , 88 rationalization of intermetallic catalytic synergies should not overlook other structural features, such as local coordination, 73 , 89 for accurate analysis of orbital hybridization and charge transfer effects.…”
Section: Engineering Strategiesmentioning
confidence: 99%
“…Precise regulation and an in-depth understanding of the atom-scale effect suggested that the heteronuclear dual SA and SA dimers exhibit an improved atomic interface (Figure 12d) for electrochemical energy generation and reduction processes. [144,207,208] The dynamic atomiclevel structure under conditions of alkaline HER is influenced by the electrochemical properties of the active sites, which are a result of coordination engineering. The dynamic structure results from surface self-reconstruction and is possible to track by using atomic level identification by XANES spectral analysis.…”
Section: Emerging Atomic Species For Advanced Energy Conversionmentioning
confidence: 99%